To Be or Not to Be (Stressed): The Critical Role of a Psychologically Healthy Workplace in Effective Stress Management. (15th October 2015) - Grawitch, Matthew J.; Ballard, David W.; Erb, Kaitlyn R.
Abstract This article explains how key practices pertaining to the psychologically healthy workplace can be used to develop a comprehensive approach to stress management in contemporary organizations. Specifically, we demonstrate the ways in which employee involvement, recognition, work–life balance, health and safety, and growth and development practices can be used to assist in the reduction of work stress and the proactive management of strain. Although many organizations strive to establish a positive environment conducive to work and well‐being, identifying where to begin can often seem like a daunting task. Currently, many stress management efforts emphasize individual‐level interventions that are simply implemented alongside existing organizational practices. We propose that a broader perspective allows for a better understanding of the stress process, resulting in the ability to consider a wider range of changes to organizational processes. Combining knowledge regarding psychologically healthy workplace practices, stress management intervention levels and the personal resource allocation framework, we present a comprehensive framework for approaching workplace stress management, which can be tailored to the unique needs of various organizations, departments and employees. By adopting this broader perspective, we believe organizations can more strategically address employee stress, resulting in more effective stress management and a profound impact on stress‐related outcomes. Copyright © 2014 John Wiley & Sons, Ltd.